2019
DOI: 10.1108/par-10-2017-0085
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing sustainability reporting by Sri Lankan companies

Abstract: Purpose This paper aims to investigate the key company characteristics which influence sustainability reporting by publicly listed companies in Sri Lanka. Design/methodology/approach Panel data analysis is conducted to analyse sustainability reporting of 84 publicly listed companies from 2012 to 2015. Findings Company size and usage of the GRI guidelines are found to be the most relevant company characteristics associated with sustainability reporting by listed companies in Sri Lanka. Unexpectedly, ownersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 77 publications
7
104
1
6
Order By: Relevance
“…Some authors, for example, have proved that the company size (usually measured by the number of employees, total assets, sales or market capitalization) has a positive influence on the decision or the likelihood of a company to engage in sustainability reporting (Janggu et al 2007;Gallo and Christensen 2011;Das et al 2015;Schreck and Raithel 2018;Dissanayake et al 2019). According to these authors, the positive relationship can be explained by the greater public visibility (and pressure) that large companies have to face (Fortanier et al 2011;Fernando and Pandey 2012;Fernando et al 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors, for example, have proved that the company size (usually measured by the number of employees, total assets, sales or market capitalization) has a positive influence on the decision or the likelihood of a company to engage in sustainability reporting (Janggu et al 2007;Gallo and Christensen 2011;Das et al 2015;Schreck and Raithel 2018;Dissanayake et al 2019). According to these authors, the positive relationship can be explained by the greater public visibility (and pressure) that large companies have to face (Fortanier et al 2011;Fernando and Pandey 2012;Fernando et al 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given the increasing concern for the global environmental issues and the relating need for preservation of the ecosystem, sustainability reporting has become more and more important, to both developed and developing economies, sparking the interest of the literature (Hahn and Kühnen 2013). Consequently, an increasing number of scholars has started to analyse the factors influencing the adoption of new sustainability methods in business reporting (Bear et al 2010;Da Silva Monteiro and Aibar-Guzmán 2010;Gallo and Christensen 2011;Gamerschlag et al 2011;Arayssi et al 2016;Ben-Amar et al 2017;Anazonwu et al 2018;Dissanayake et al 2019). Prior studies also have analysed the adoption of external assurance of sustainability reporting in order to increase the transparency of the sustainability information disclosed and enhance stakeholders' confidence (Kolk and Perego 2010;Moroney et al 2012;Junior et al 2014;Peters and Romi 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In India, most companies disclose sustainability/CSR information in standalone reports and show a constructive change in the mode of disclosures (Jain & Winner, 2016). The average word count in sustainability reporting has been showing an increasing trend from the year 2012 (2264 words) to 2015 (3039 words) in Sri Lanka (Dissanayake et al, 2019). Orazalin and Mahmood (2019) found that standalone reporting, reporting language, profitability, size, and auditor type influenced the nature, extent, and quality of sustainability reporting among Kazakhstani companies for the years of 2013-2015.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The selected sectors are Textile, Cement, Food & Allied, Pharmaceuticals & Chemicals, and Bank as these industries contribute the most to the economic development of Bangladesh. Banks are leading in the disclosure of corporate social activities, social and environmental reporting, and sustainability reporting (Dissanayake et al, 2019). The rationale for selecting the manufacturing industries is that manufacturing activities gradually worsen environmental hazards such as global warming; biodiversity degradation; and air, water, soil, and marine pollutions.…”
Section: Sample Selectionmentioning
confidence: 99%
“…Sustainability reporting in the Asian region is also a growing area of research interest. To this end, Dissanayake et al (2019) aim to investigate the key company characteristics which influence sustainability reporting by publicly listed companies in Sri Lanka. They use panel data to analyse sustainability reporting of 84 publicly listed companies.…”
mentioning
confidence: 99%